ANALISIS PENGARUH UPAH MINIMUM, INVESTASI DAN PENGELUARAN PEMERINTAH TERHADAP PENYERAPAN TENAGA KERJA BERDASARKAN PENDIDIKAN - Wilis, Retno (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2015)
This study analyzes the influence of the minimum wage, investment and gov-ernment spending on educated employment, trained employment and unedu-cated and untrained employment in 38 Regencies/Cities of East Java Provincein 2008–2013. The research is using quantitative approach, panel data analysisand Fixed Effect Model (FEM) method. The results show that the minimumwage variable has negative significant effect on the educated employment,trained employment and uneducated and untrained employment. Regionalinvestment variable does not significantly affect to the educated employment,trained employment and uneducated and untrained employment. Domesticinvestment variable has positive significant effect on the trained employment,but does not significantly affect to the educated employment and uneducatedand untrained employment. Foreign investment variable does not significantlyaffect to the educated employment, trained employment and uneducated anduntrained employment. And government spending variable has positive sig-nificant effect on the educated employment and uneducated and untrainedemployment, but does not significantly affect to the trained employment